Smart Plug Socket with ESP-NOW and MQTT for Efficient Power Monitoring and Control via Android - Dhananjaya, Anak Agung Ngurah Gede; Suarjaya, I Made Agus Dwi; Almantara, I Putu Sugi (JITTER: Jurnal Ilmiah Teknologi dan Komputer, 2025)
Uncontrolled electricity usage and voltage fluctuations can damage electronic devices and lead to energy waste. This research designs a plug socket system capable of efficiently monitoring and controlling electricity consumption through an Android application. The system consists of two devices: a master and a slave, communicate using the ESP-NOW protocol without an internet connection, and connect to the Android app via MQTT. The slave device, equipped with a PZEM-004T sensor to monitor electrical parameters such as voltage, current, power, and energy. The system is designed to automatically cut off power if voltage fluctuations occur for more than one minute and to restore it when the voltage returns to normal. The Android application provides features such as relay control, scheduling, cost estimation, and historical data visualization for up to 45 days. Testing results shows the system functions well and assists users in monitoring and controlling electricity use more efficiently and safely.